Job search and (re)employment: taking the time-varying nature of job-search intensity into consideration - Galić, Zvonimir (2011)
The aim of this study was to test the hypothesis that job-search intensity has a pivotal role for (re)employment of unemployed individuals. In our study we tested a heuristic model that included sets of variables potentially influencing (re)employment. Those were: biographic characteristics, employment motivation factors, job search constraints, and job-search intensity. We expected job-search intensity to be the most important determinant of (re)employment, at the same time representing the mechanism through which other variables of the model affect (re)employment probability. The model was tested on the data collected within a longitudinal multi-wave study on a large and heterogeneous sample of unemployed people from Croatia. Our results showed that, when its dynamic nature is taken in consideration, job-search intensity represents an important determinant of (re)employment, partially mediating effect of other predictor variables. However, more important predictors of (re)employment were biographic characteristics of the unemployed and their financial situation which influenced (re)employment directly, independently of job-search intensity.
Projekt MZOS
ENG